EFEKTIVITAS ANTIBAKTERI KITOSAN CANGKANG KEPITING BAKAU (SCYLLA SERRATA) TERHADAP PERTUMBUHAN STREPTOCOCCUS MUTANS DAN PORPHYROMONAS GINGIVALIS - Mellani Cindera Negara; Sulistiawati .; Shafa Al-Afifah Silparensi; Muhammad Rizki Ramadhan; Trisnawaty Trisnawaty; Listia Eka Merdekawati (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2026)
Streptococcus mutans and Porphyromonas gingivalis are major pathogenic bacteria involved in dental and periodontal diseases, such as caries and periodontitis. Chitosan derived from mangrove crab shells (Scylla serrata) is a natural biopolymer with potential antibacterial activity. This study aimed to evaluate the antibacterial effect of chitosan against Streptococcus mutans and Porphyromonas gingivalis based on inhibition zone diameters at concentrations of 0.25%, 0.5%, and 1%. An in vitro disk diffusion method was applied using 0.2% chlorhexidine as a positive control and distilled water as a negative control. The results showed that chitosan produced inhibition zones against both bacteria, with diameters increasing along with the concentration. The largest inhibition zone was observed at 1%, while smaller zones were formed at 0.25% and 0.5%. In conclusion, chitosan from mangrove crab shells exhibits antibacterial activity against Streptococcus mutans and Porphyromonas gingivalis, although its inhibitory effect remains lower than the positive control.